Fatty acid content and composition in edible Ruspolia differens feeding on mixtures of natural food plants - Rutaro, Karlmax; Malinga, Geoffrey M.; Lehtovaara, Vilma J.; Opoke, Robert; Nyeko, Philip; Roininen, Heikki; Valtonen, Anu (BMC Research Notes, 2018)
To develop successful mass-rearing programs of edible insects, knowledge of the feeds and their influence on nutritional content is critical. We assessed the influence of natural food plants (grass inflorescences) and their mixtures on fatty acid profiles of edible Ruspolia differens. We reared neonate nymphs to adult on six dietary treatments consisting of one, and mixtures of two, three, five, six and eight plants. Results: The contents of saturated, monounsaturated and polyunsaturated fatty acids, omega-6/omega-3 ratio, and adult body weight did not differ among dietary treatments. However, the composition of fatty acids differed significantly among insects fed on six dietary treatments, but only for the rare fatty acids. Our results demonstrate that even if natural diets (grass inflorescences) do not strongly modify fatty acid contents or compositions of R. differens, when reared from neonate nymphs to adults, their n − 6/n − 3 fatty acid ratio is generally low and thus good for a healthy human diet.
Keywords: Africa; Edible insect; Food security; Natural diets; MUFA; PUFA